1995
DOI: 10.1161/01.cir.91.7.1929
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Increase in Thrombin Generation and Activity After Cessation of Intravenous Heparin in Patients With Acute Coronary Syndromes

Abstract: This study demonstrates a transient rebound increase in thrombin activity as well as in activated protein C upon abrupt discontinuation of intravenous heparin. Clinicians should be vigilant for associated thrombotic events. Further investigation of the significance, mechanism, and possible prevention of this rebound phenomenon is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
4
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 192 publications
(91 citation statements)
references
References 20 publications
3
82
4
2
Order By: Relevance
“…Alternatively, prolonged heparin duration may cause more pronounced platelet activation or buildup of thrombin or identify a subset of patients with more unstable symptoms requiring prolonged heparin therapy. A prior study, however, found that the increase in thrombin generation and activation seen after heparin discontinuation was not associated with duration of heparin therapy, 8 which argues against this as a mechanism for the observed risk of prolonged therapy in our study. A repeat multivariate analysis in our population limited to those who were on study drug at the time of heparin withdrawal (data not shown) showed that prolonged heparin infusion actually provided a protective effect.…”
Section: Discussioncontrasting
confidence: 65%
“…Alternatively, prolonged heparin duration may cause more pronounced platelet activation or buildup of thrombin or identify a subset of patients with more unstable symptoms requiring prolonged heparin therapy. A prior study, however, found that the increase in thrombin generation and activation seen after heparin discontinuation was not associated with duration of heparin therapy, 8 which argues against this as a mechanism for the observed risk of prolonged therapy in our study. A repeat multivariate analysis in our population limited to those who were on study drug at the time of heparin withdrawal (data not shown) showed that prolonged heparin infusion actually provided a protective effect.…”
Section: Discussioncontrasting
confidence: 65%
“…443, 444 The combination of UFH and ASA appears to mitigate this reactivation in part, 442,445 although there is hematologic evidence of increased thrombin activity after the cessation of intravenous UFH ("rebound") even in the presence of ASA. 446 Uncontrolled observations suggested a reduction in the "heparin rebound" by switching from intravenous to subcutaneous UFH for several days before the drug is stopped.…”
Section: Unfractionated Heparinmentioning
confidence: 99%
“…544, 545 The combination of UFH and ASA appears to mitigate this reactivation in part, 543,546 although there is hematologic evidence of increased thrombin activity after the cessation of intravenous UFH ("rebound") even in the presence of ASA. 547 Uncontrolled observations suggested a reduction in the "heparin rebound" by switching from intravenous to subcutaneous UFH for several days before the drug is stopped.…”
Section: Unfractionated Heparinmentioning
confidence: 99%